Karakter Morfologi dan Kimia Kultivar Pamelo (Citrus maxima (Burm.) Merr.) Berbiji dan Tanpa Biji - Arifah Rahayu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
The objective of this study was to evaluate morphological and chemical characteristics of seeded and seedless pummelofruit. The study was carried out during April 2009 to July 2010. The pummelo fruits were harvested from the productioncenter of Sumedang, Pati, Kudus, Magetan, Bireun (Aceh) and Pangkep (South Sulawesi). Some of seeded cultivars havespherical and ellipsoid form, while the seedless one shown pyriform shape. The edible portion of the fruits (juice vesicles)mainly affected by peel thickness and fruit shape. The edible portion of seedless cultivars (57.22%) were not sigificantlydifferent with seeded (57.07%) and potentially seedless cultivars (59.35%). Generally fruit taste of seedless cultivars weresweet to sweet-bitter, meanwhile seeded and potentially seedless pummelo cultivars have sour-sweet. Pummelo juice tastewas affected by TSS (total soluble solids), TA (titratable acidity), TSS/TA ratio and naringin content. Seedless pummelocultivars have higher pH, TSS, TSS/TA ratio, vitamin C and naringin, but lower in TA content than seeded and potentiallyseedless fruit juice. ‘Jawa 1’ and ‘Bali Merah 2’ pummelos can be further developed as seedless superior cultivars.Keywords: fruit shape, edible portion, TSS/TA, naringin, vitamin C